The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1103/physrevlett.104.164301
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Surface Evanescent Wave and its Dominant Contribution to Extraordinary Acoustic Transmission and Collimation of Sound

Abstract: We demonstrate both theoretically and experimentally the physical mechanism that underlies extraordinary acoustic transmission and collimation of sound through a one-dimensional decorated plate. A microscopic theory considers the total field as the sum of the scattered waves by every periodically aligned groove on the plate, which divides the total field into far-field radiative cylindrical waves and acoustic surface evanescent waves (ASEWs). Different from the well-known acoustic surface waves like Rayleigh w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 27 publications
2
85
0
Order By: Relevance
“…Note that the dipole-like radiation phenomenon occurs when the wavelength (l ¼ 40 mm) is much larger than the period of the HRs (d ¼ 8 mm), which can be utilized to realize device miniaturization. As no sidelobes occur in the pattern, the pattern is not due to the excitation of the acoustic surface wave emerging only in the vicinity of the resonant transmission peak 20 . Actually, the dipole-like radiation pattern can occur in a very wide bandwidth, which is illustrated below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the dipole-like radiation phenomenon occurs when the wavelength (l ¼ 40 mm) is much larger than the period of the HRs (d ¼ 8 mm), which can be utilized to realize device miniaturization. As no sidelobes occur in the pattern, the pattern is not due to the excitation of the acoustic surface wave emerging only in the vicinity of the resonant transmission peak 20 . Actually, the dipole-like radiation pattern can occur in a very wide bandwidth, which is illustrated below.…”
Section: Resultsmentioning
confidence: 99%
“…It may seem that our system is similar to that of a single slit surrounded by finite, periodically perforated grooves; however, the experimental phenomenon and the mechanism of our system are quite different. The directional beam experimental report by Zhou et al 20 showed very strong fingerprints of the running surface wave scattered by the grooves [20][21][22] , and the directional beam occurred in a very narrow bandwidth. We verify that the dipole-like pattern radiation phenomenon in our samples arises from the effective boundary impedance adjustment.…”
mentioning
confidence: 99%
“…A motion picture showing the frequency dependence of the emitted beam propagating in free space is presented in the Supplemental Material Movie S3 [7]. This is not the first demonstration of funneling of acoustic energy with perforated structures, but the previous one [14,15] and the phenomenon was obtained resonantly, using acoustic surface waves. Here, on the contrary, it is a nonresonant phenomenon and consequently its bandwidth is not strongly limited.…”
Section: -2mentioning
confidence: 99%
“…Novel phenomena have been investigated, for example, enhanced light-matter interaction, ultrafast acoustoplasmonic control, and sensing by evanescent surface acoustic waves (SAWs). [1][2][3][4] Phononic nanostructures could lead to a variety of potential applications, ranging from acoustic metamaterials, self-collimation, sound isolation, and heat management to compact acoustic waveguides. [5][6][7][8][9] Similar to their photonic counterparts, the flexibility to tailor the acoustic properties of phononic crystals (PnCs) and PnC waveguides makes them particularly suitable for a wide range of applications from transducer technology to filtering, guiding, and demultiplexing of acoustic waves.…”
Section: Introductionmentioning
confidence: 99%